Functional Molecular Diversity of Marine Dissolved Organic Matter Is Reduced during Degradation - Mentges, Andrea; Feenders, Christoph; Seibt, Maren; Blasius, Bernd; Dittmar, Thorsten (Frontiers in Marine Science, 2017)
Dissolved organic matter (DOM) is a highly diverse mixture of compounds, accounting for one of the world's largest active carbon pools. The surprising recalcitrance of some DOM compounds to bacterial degradation has recently been associated with its diversity. However, little is known about large-scale patterns of marine DOM diversity and its change through degradation, in particular considering the functional diversity of DOM. Here, we analyze the development of marine DOM diversity during degradation in two data sets comprising DOM of very different ages: a three-year mesocosm experiment and highly-resolved field samples from the Atlantic and Southern Ocean. The DOM molecular composition was determined using ultra-high resolution mass spectrometry. We quantify DOM diversity using three conceptually different diversity measures, namely richness of molecular formulas, abundance-based diversity, and functional molecular diversity. Using these measures we find stable molecular richness of DOM with age >1 year, systematic changes in the molecules' abundance distribution with degradation state, and increasing homogeneity with respect to chemical properties for more degraded DOM. Coinciding with differences in sea water density, the spatial field data separated clearly into regions of high and low diversity. The joint application of different diversity measures yields a comprehensive overview on temporal and spatial patterns of molecular diversity, valuable for general conclusions on drivers and consequences of marine DOM diversity.